Trends and challenges in valorisation of food waste in developing economies: A case study of India. (December 2021) - Sinha, Sujata; Tripathi, Pushplata
Abstract: Food waste regardless of the production site is either disposed of in landfill sites or is treated biologically or chemically for reducing environmental problems. India, China, the USA, and Brazil produce most food waste in the world. Landfill and composting are traditional methods for food waste management and disposal in developing economies but are not considered feasible due to toxic gases released, bad odour, and environmental pollution associated with it. However, stricter regulation and demand for renewable chemicals/fuels production led to increased research in areas of food waste valorisation. Bioethanol, biodiesel production for green fuel, and production of other industrially useful chemicals by green synthesis are upcoming research areas. This article aimed to cover existing ways of first-generation food waste processing which has been reported in developing economies like India. Changes in existing legislation over time according to changing food waste disposal scenarios in India have been highlighted. The gradual shifting of food waste management from a linear to a circular economy has been shown through case studies. Food waste is being treated as a resource via upcoming green technologies like green fuel production using anaerobic digestion and chemical production and possible future directions have also been covered.